Peran Guru BK dalam Penanaman Karakter Disiplin dan Kejujuran di SD Aisyiyah Unggulan Gemolong Tahun Ajaran 2016/2017 - Saputro, Gunawan; , Drs. Saring Marsudi, SH. M.Pd (2017)
This study aims to determine the role : (1) the role of the teacher BK in the planting of character discipline and honesty in SD Aisyiyah seed Gemolong, (2) the constraints in the planting of character discipline and honesty in SD Aisyiyah seed Gemolong, and (3 ) solutions in the cultivation of character discipline and honesty in SD Aisyiyah seed Gemolong. This study is included in a descriptive qualitative research, the research informants are principals, teachers Counseling, teachers involved, and students. Data collection techniques of interview, observation and documentation. Data were analyzed by means of data reduction, data presentation, and then draw conclusions. Mechanical examination of the validity of data by using triangulation of sources and techniques. The results showed that (1)teachers BK role as educator of the child's character development one disciplinary character and honesty, because it teaches discipline and honesty of character is very important for the future of the students.(2)Constraints faced by teachers Counseling in instilling discipline and honesty of character is the cooperation with the parents, because the parents mostly busy at work, so less attention to the character of children.(3)Solutions to overcome the difficulty of co-operation with parents Counseling teachers usually do home visit to resolve the problems faced by students, and then find a way out together with parents.